Time course of EEG activities in continuous tracking task: a pilot study. (31st October 2017) - Yang, Limin; Shen, Liyi; Nan, Wenya; Tang, Qi; Wan, Feng; Zhu, Frank; Hu, Yong
Abstract: Motor learning is crucial to surgical skills enhancement, but its neural mechanism has been investigated only using some simple tasks with limited motor involvement. This study aimed to gain more understanding of the neural dynamics during motor learning by investigating the time course of electroencephalogram (EEG) activities in the continuous tracking task that involves more motor components. One participant performed 16 trials of the continuous tracking task on Day1 and Day2 respectively. The 16-channel EEG signals were recorded and analyzed in both the resting and active states. Results showed that the tracking performance improved from Day1 to Day2. Regarding the EEG, it was found that the relative amplitude in the individual alpha band (IAB) decreased locally over primary motor cortex from the resting state to the active state on both days, and this reduction was more focused on the left primary motor cortex on Day2 compared to Day1. Moreover, in the active state the alpha coherence between central and frontal areas also significantly increased from Day1 to Day2. Time course of alpha activities may explain the tracking performance enhancement from Day1 to Day2. Future work will include more participants to extend the validity of current results.